Computer-assisted interpretation of planar whole-body bone scintigraphy in patients with newly diagnosed prostate cancer. Issue 7 (July 2015) - Petersen, Lars J.; Mortensen, Jesper C.; Bertelsen, Henrik; Zacho, Helle D.
<x xml:space="preserve">Abstract</x> Purpose The aim of this study was to compare the diagnostic properties of EXINI BoneBSI in newly diagnosed prostate cancer in comparison with expert reading. Materials and methods Bone scintigraphy was performed in consecutive patients referred for staging at three clinics (342 patients with DICOM file format, 272 with Interfile format). Images were reported by three independent readers on a four-point scale (class 1–4) and by using a dichotomous outcome (M1 or M0). The software analyzed data in balanced mode, as well as using 'patient-specific' settings (based on tumor characteristics), and classified outcome as normal (N), probably normal (pN), probably abnormal (pA), and abnormal (A). Results Classification of bone metastasis using the software (pA+A) versus experts (class 3+4) showed a sensitivity of 93.3%, specificity of 89.3%, positive predictive value of 57.5%, and negative predictive value of 98.9% with DICOM files. The diagnostic properties of the software were notably different with Interfile format. For example, expert M1 versus software A showed a sensitivity of 90.0%, specificity of 98.9%, positive predictive value of 88.2%, and negative predictive value of 98.3% with DICOM files, versus 69.2, 88.2, 38.3, and 96.4% with Interfile format, respectively. Generally, patient-specific settings did not influence the diagnostic characteristics of the software versus balanced setting with expert reading as reference. Conclusion EXINI BoneBSI showed high sensitivity and specificity for bone metastasis in patients with newly diagnosed prostate cancer. The software ruled out metastasis with confidence, whereas the positive predictive value was modest. The diagnostic properties were different for DICOM and Interfile file formats.